Human Resources Management's Role Through Learning Opportunities in Turnover Intention of Jakarta’s Education Sector - Sonny Prasetyo; Edi Hamdi (Annals of Human Resource Management Research, 2026)
Purpose: This study explored the role of Human Resource Management (HRM) through programs that support learning opportunities and their influence on employee turnover intentions in Jakarta's education industry. Research Methodology: Data were collected through online surveys of school employees and teachers in Jakarta. A Structural Equation Model (SEM) was used with HRM and internal communication as independent variables, learning opportunities and turnover intentions as dependent variables, and internal communication as a moderator between HRM and turnover intention. Results: HRM reduces turnover intention and increases learning opportunities. Learning opportunities and internal communication have no significant effect on turnover intention, and internal communication does not moderate the HRM–turnover link. Conclusions: In Jakarta’s education industry, effective HRM is key to reducing turnover and fostering learning opportunities, while internal communication and learning opportunities play limited roles in influencing turnover. Limitations: Several factors need to be considered to determine whether they are suitable for the selected demographic. These differences can ultimately enrich our knowledge and insights into the situations and conditions around us. Contributions: This study aims to provide insights for organizations in planning investments through HRM programs that support learning opportunities as a way to reduce employee turnover.